Post-Fire School Preparedness Analysis: A Case Study of Public Junior High Schools in Samarinda City - Febbi Mawanda; Mei Vita Romadon Ningrum; Nurul Azmi; Juwari Juwari (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2026)
Samarinda City, the capital of East Kalimantan Province, has the highest fire incident rate in the province, with 158 incidents recorded from January to October 2025. Schools as educational institutions have a high vulnerability to fire disasters. This study aims to analyze the preparedness of public junior high schools (SMP) in fire-prone areas of Samarinda City in facing fire disasters. The study used a qualitative method with a case study approach in two schools, namely SMP Negeri 5 Samarinda and SMP Negeri 37 Samarinda. Data collection techniques through in-depth interviews, observation, and document studies. Data analysis used the Miles and Huberman model and the three-pillar framework of Disaster Safe Education Units (SPAB). The results showed that SMP Negeri 5 Samarinda had quite good preparedness in terms of physical facilities (25 units of APAR, assembly points, easy firefighter access) but weak in management and education aspects. SMP Negeri 37 Samarinda was at the unprepared level in all SPAB pillars because it only had 1 unit of APAR, no evacuation route, assembly points, or firefighter access. Both schools had never conducted a fire simulation. This study recommends the need for formal policies, the formation of disaster preparedness teams, and the implementation of regular fire simulations.